Ethical criteria when a (potential) perpetrator asks a human rights organization to defend their case based on the forensic documentation of alleged torture. How shall we proceed? Debate - López Martín, Sara (Torture Journal, 2020)
Objective Discuss the ethical dilemma of perpetrators requesting clinical evaluations intended to prove persecution or torture. The discussion is organized around three real cases. Method We present three cases of plausible perpetra- tors, partially amended to protect anonymity. The paper presents a review of the complex ethical challenges that the dilemma poses. A multidisciplinary panel of doctors, psychologists and lawyers had a similar discussion and agreed on three criteria presented here for contrast with the broader community of researchers and practitioners. The paper is not in itself a legal or ethical academic review, instead, it establishes the main terms of debate, demonstrates the lack of literature that debates it and reflects an initial consensus between forensic workers in an independent human rights organization.